Liver Transplantation Despite Active Intracranial Hemorrhage in Acetaminophen‐Induced Acute Liver Failure: A Case Report - Daryna Shnitser; Eslam Fouda; Ramona Nicolau‐Raducu; Fouad G. Souki (Clinical Case Reports, 2026)
ABSTRACT Acute liver failure with intracranial hemorrhage poses difficult transplant decisions. We report acetaminophen‐induced acute liver failure with cerebral edema and active multifocal hemorrhage successfully managed with emergent liver transplantation and staged neurosurgical intervention. This case supports individualized transplantation when hepatic prognosis is fatal and neurologic recovery remains plausible.